2016
DOI: 10.1016/j.jeconom.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian treatment effects models with variable selection for panel outcomes with an application to earnings effects of maternity leave

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Jacobi et al . () consider the 2000 reform in Austria which increased the period of paid leave from 18 to 30 months. It is clear that this reform extended the amount of maternity leave taken by a substantial amount.…”
Section: Changing the Duration Of Paid Parental Leavementioning
confidence: 99%
See 2 more Smart Citations
“…Jacobi et al . () consider the 2000 reform in Austria which increased the period of paid leave from 18 to 30 months. It is clear that this reform extended the amount of maternity leave taken by a substantial amount.…”
Section: Changing the Duration Of Paid Parental Leavementioning
confidence: 99%
“…Dahl et al conclude that these payments are expensive with little effect and come at a high cost both in absolute terms and in terms of redistributing income to high-and middle-income families. Jacobi et al (2016) consider the 2000 reform in Austria which increased the period of paid leave from 18 to 30 months. It is clear that this reform extended the amount of maternity leave taken by a substantial amount.…”
Section: (I) Single-country Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our proposed method can be seen as an alternative to Wang et al (2012), with certain conceptual and computational advantages, namely ease of prior specification and posterior sampling. Other papers elaborating upon this approach include Wang et al (2015), Lefebvre et al (2014) and Talbot et al (2015); see also Jacobi et al (2016). Zigler and Dominici (2014) and An (2010) focus on Bayesian propensity score models (for use with binary treatment variables).…”
Section: Variablementioning
confidence: 99%
“…Consequently, mothers continue to have the main responsibility for unpaid care and family work. Recent findings have shown that fathers, even if they have been on parental leave or have worked part-time, experienced significantly fewer negative consequences with regard to career and salaries than mothers, as their leave periods are, for the most part, shorter and their part-time work mainly involves more working hours than mothers' part-time work (Glauber 2019;Bünning 2016;Jacobi et al 2016;Schiffbänker and Holzinger 2014). Furthermore, research from Germany has revealed a strong correlation between company structures and fathers' working hours: when companies are characterized by official, general, and transparent rules, fathers are more likely to work reduced hours (Bernhardt and Bünning 2017).…”
Section: Parents At Their Workplace-general Evidence and Research Gapmentioning
confidence: 99%